ТЕОРЕТИКО-ПРАВОВІ ЗАСАДИ ФОРМУВАННЯ КУЛЬТУРИ ТОЛЕРАНТНОСТІ В ДІЯЛЬНОСТІ СУБ’ЄКТІВ ПОДАТКОВИХ ПРАВОВІДНОСИН - Ничипоренко, Олексій Валентинович (SUPREMANCE OF LAW, 2017)
The article examines the theoretical and legal features of a culture of tolerance in the activities of tax legal proceeding primarily with theoretical and methodological possibilities lyudynotsentrystskoho approach. The necessity of separation of the theoretical and legal, regulatory and process levels pravorealizatsiynoho creating a culture of tolerance.
Keywords: tolerance; human dignity; the culture of tolerance.